2012
DOI: 10.1097/nen.0b013e31825414a6
|View full text |Cite
|
Sign up to set email alerts
|

Miglustat Improves Purkinje Cell Survival and Alters Microglial Phenotype in Feline Niemann-Pick Disease Type C

Abstract: Niemann-Pick disease type C (NPC disease) is an incurable cellular lipid trafficking disorder characterized by neurodegeneration and intralysosomal accumulation of cholesterol and glycosphingolipids. Treatment with miglustat, a small imino sugar that reversibly inhibits glucosylceramide synthase, which is necessary for glycosphingolipid synthesis, has been shown to benefit patients with NPC disease. The mechanism(s) and extent of brain cellular changes underlying this benefit are not understood. To investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 64 publications
1
77
0
Order By: Relevance
“…150 ). In the feline model of NPC disease, miglustat decreased GM2 ganglioside accumulation and slightly delayed development of neurological symptoms ( 151 ). Similarly, in Npc1 Ϫ / Ϫ mice, miglustat reduced ganglioside storage in LEs/Ls.…”
Section: Cyclodextrin As a Therapy For Npc Diseasementioning
confidence: 99%
“…150 ). In the feline model of NPC disease, miglustat decreased GM2 ganglioside accumulation and slightly delayed development of neurological symptoms ( 151 ). Similarly, in Npc1 Ϫ / Ϫ mice, miglustat reduced ganglioside storage in LEs/Ls.…”
Section: Cyclodextrin As a Therapy For Npc Diseasementioning
confidence: 99%
“…Alternatively, miglustat may exert its effects through nonlipid storage or downstream pathways, or by enhancing neuronal survival through other mechanisms. Indeed, a recent study examining the effi cacy of miglustat in the feline NPC1 model revealed dramatic rescue of Purkinje neurons despite only modest effects on sphingolipid storage ( 26 ). Nonetheless, treatment of NPC1 patients with the sphingolipid synthesis inhibitor was associated with signifi cant reductions (LacCer and GM1 and GM3 gangliosides) and elevations (MC) in multiple circulating sphingolipid species.…”
Section: Figmentioning
confidence: 99%
“…The clinical, neuropathological, and biochemical abnormalities present in juvenile-onset patients are similarly faithfully modeled in a naturally-occurring feline model of NPC disease, which has a missense mutation in the Npc1 gene ( 19,20 ). Intervention with miglustat, an inhibitor of glycosphingolipid biosynthesis, or 2-hydroxypropyl-␤ -cyclodextrin (HP-␤ -CD), a cholesterol-binding agent, alleviates neuronal ganglioside (miglustat and HP-␤ -CD) and cholesterol (HP-␤ -CD) storage in the NPC1 mouse model, and markedly prolongs survival in NPC1 mouse and cat models (21)(22)(23)(24)(25)(26). These promising preclinical studies have led to administration of HP-␤ -CD in four NPC1 patients through the investigatorsponsored single-patient Investigational New Drug program in the USA and two NPC1 patients in Japan ( 27 ), and laid the groundwork for a Phase 1 trial for HP-␤ -CD that was initiated in January 2013 at the National Institutes of Health (NIH).…”
Section: Npc1mentioning
confidence: 99%
“…Treatment of NPC mice with miglustat resulted in improvements of survival in these mice ( 41 ). In a cat model of NPC disease, miglustat delayed the onset of neurological symptoms and improved survival ( 42 ). These effects were associated with improved survival of cerebellar Purkinje cells and reduced micogliosis and infl ammatory markers.…”
Section: Approaches To Therapeutic Interventionmentioning
confidence: 91%